2013
DOI: 10.1007/s11060-013-1168-5
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine synthetase functions as a negative growth regulator in glioma

Abstract: Our recent study demonstrated that glutamine synthetase (GS) may not only serve as a glutamate-converting enzyme in glial cells, but may also function as a regulator of astrocyte migration after injury. In this report, we showed that GS expression increased in cultured rat C6 glioma cells that underwent long-term serially propagation. The stable overexpression of GS in C6 glioma cells resulted in growth arrest and motility suppression; however the stable knockdown of GS resulted in motility enhancement. In cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
2
10
1
Order By: Relevance
“…Despite all of this evidence, we did not observe GUO effects on glutamate uptake, release, or GS activity, an enzyme that had been considered as a negative growth regulator in glioma cells [42]. Additionally, the pharmacological blockade of glutamate receptors or transporters did not interfere with the cytotoxic effect of GUO.…”
Section: Discussioncontrasting
confidence: 65%
“…Despite all of this evidence, we did not observe GUO effects on glutamate uptake, release, or GS activity, an enzyme that had been considered as a negative growth regulator in glioma cells [42]. Additionally, the pharmacological blockade of glutamate receptors or transporters did not interfere with the cytotoxic effect of GUO.…”
Section: Discussioncontrasting
confidence: 65%
“…Whether downregulation of GS mechanistically contributes to glutamate accumulation and seizure generation or other phenotypic parameters of glioma cells remains an open question. While the studies mentioned above indicate that low GS levels could be beneficial for GBM patients, the only experimental study performed so far showed that overexpression of GS resulted in growth arrest and motility suppression of rat C6 glioma cells in an N-cadherin-dependent manner while GS silencing enhanced cell motility [120]. Further studies are needed in order to conclude whether GS acts as a proor anti-glioma enzyme.…”
Section: Modulation Of Gs and Gludmentioning
confidence: 96%
“…Colony formation assay was used to measure the ability of a single cell to grow into a colony [16]. In brief, before harvesting from donor cultures, 4 randomly selected stable glioma cell lines in individual group were serum starved for 24 h. After trypsinized to produce a single-cell suspension, the cells were diluted into 50 cells per well and seed on 6-well plate.…”
Section: Colony Formation Assaymentioning
confidence: 99%
“…To investigate subcellular distribution of proteins, nuclear and cytoplasmic fractions were enriched using Nuclear and Cytoplasmic Protein Extraction Kit (CoWin Bioscience, China).Western blot analysis was performed as previously reported [16]. …”
Section: Western Blotmentioning
confidence: 99%